Efektivitas Pupuk Organik pada Tumpangsari Kedelai dengan Jagung untuk Mengurangi Penggunaan Pupuk N, P dan K - Evi Oktanika; Supriyono Supriyono; Suwarto Suwarto (Agrosains : Jurnal Penelitian Agronomi, 2013)
Soybean is one of the commodity with high market demand. Soybean production process is limited by the lack of land. One of the efforts to improve the usefullness of land and production of soybean is an intercropping method between soybean and corn. Intercropping that over using chemical fertilizers have impact negatively on the land. Therefore, utilization of organic fertilizer to reduce the chemical fertilizer is necessary to prevent the damage of the land. This study aimed to examine the utilization of organic fertilizer to replace a part of chemical fertilizer. This study was conducted at the Center for Dryland Research Faculty of Agriculture, University of Sebelas Maret Surakarta, Jumantono, Karanganyar started on February until May 2013. The experiment was conducted using Randomized Complete Block Design (RCBD) with one factor fertilization consists of 6 levels, one control and two comparators monoculture. The results showed that application of organic fertilizer 800 kg ha-1, Urea 125 kg ha-1, SP-36 83.33 kg ha-1 and KCl 83.33 kg ha-1 with the highest yield for soybean 1.52 tons ha-1 and corn 1.25 tons ha-1 is optimal balance dosage of organic and inorganic fertilizers to soybean-corn intercropping. The treatment did not significantly different with inorganic fertilizer intercropping experiment. The research treatment showed that N, P and K fertilizer can’t be reduce by organic fertilizers.